Production of Iron Oxide Nanoparticles from Ulva Lactuca with Green Synthesis for Use in Dye Adsorption - Kocer, Anil Tevfik; Inan, Benan; Ozcimen, Didem (Mehmet Sinan Bilgili, 2020)
Nanotechnology is one of the most popular subjects used in very important fields such as medicine, biotechnology and chemistry, thanks to its small size, large surface area and superior physical properties. In this context, the production of nanoscale particles is also very important. Physical and chemical methods, which are traditional, may require complex, costly and environmentally harmful processes. So, the researchers turned to green synthesis, an easy, inexpensive and environmentally friendly method for nanoparticle production. With this method, different molecules in the extracts of sources such as plants, fungi, macro, and microalgae are used to reduce metal ions to nanoparticles. Metallic nanoparticles such as silver, gold, copper, zinc, and iron produced by this method can be used in fields such as medicine, biomedical, chemistry, and environment thanks to its many important superior features. Iron-based nanoparticles have a fairly high capacity to remove various pollutants from wastewater. In this study, iron-oxide nanoparticles (IO-NP) were synthesized from Ulva lactuca macroalgae extracts by green synthesis method, and synthesized nanoparticles were used for adsorption of Remazol Brilliant Blue R (RBBR). According to the obtained results, it was found that iron-oxide nanoparticles have high RBBR adsorption capacity than other adsorbents and they can be used as an adsorbent for removal of RBBR.
Keywords: Green Synthesis; Iron-oxide Nanoparticles; Ulva lactuca; Dye Adsorption; BRILLIANT BLUE R; METAL NANOPARTICLES; REMOVAL; OPTIMIZATION; EQUILIBRIUM; CARBON; Engineering; Environmental Sciences & Ecology